Analyzing Consistency of Formal Requirements - Becker, Jan Steffen (Electronic Communications of the EASST, 2019)
In the development of safety-critical embedded systems, requirements-driven approaches are widely used. Expressing functional requirements in formal languages enables reasoning and formal testing. This paper proposes the Simplified Universal Pattern (SUP) as an easy to use formalism and compares it to SPS, another commonly used specification pattern system. Consistency is an important property of requirements that can be checked already in early design phases. However, formal definitions of consistency are rare in literature and tent to be either too weak or computationally too complex to be applicable to industrial systems. Therefore this work proposes a new formal consistency notion, called partial consistency, for the SUP that is a trade-off between exhaustiveness and complexity. Partial consistency identifies critical cases and verifies if these cause conflicts between requirements